2021
DOI: 10.3389/fpls.2021.630243
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Gene Networks Associated With Cell Wall Components Leading to Flesh Firmness in Watermelon

Abstract: Flesh firmness of watermelon is an important quality trait for commercial fruit values, including fruit storability, transportability, and shelf life. To date, knowledge of the gene networks underlying this trait is still limited. Herein, we used weighted genes co-expression network analysis (WGCNA) based on correlation and the association of phenotypic data (cell wall contents) with significantly differentially expressed genes between two materials, a near isogeneic line “HWF” (with high average flesh firmnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 72 publications
1
17
0
Order By: Relevance
“…A plethora of studies have identified pulp firmness as the quality trait most frequently and consistently improved by grafting commercial watermelon cultivars onto inter-specific hybrid rootstocks [22,35]. This effect is associated with increased fruit cell density and altered cell wall characteristics, and it is possibly related to the grafting-mediated differentiation of scion gene expression, which encompasses the over-regulation of cytokine and other metabolites of primary and secondary metabolism [36][37][38][39]. While flesh firmness may play a crucial role in watermelon quality and may also contribute to longer shelf life, the rind thickness of the watermelon fruit by rule affects the post-harvest management and postharvest performance of the fruit [9].…”
Section: Fruit Pulp Texture and Rind Thicknessmentioning
confidence: 99%
“…A plethora of studies have identified pulp firmness as the quality trait most frequently and consistently improved by grafting commercial watermelon cultivars onto inter-specific hybrid rootstocks [22,35]. This effect is associated with increased fruit cell density and altered cell wall characteristics, and it is possibly related to the grafting-mediated differentiation of scion gene expression, which encompasses the over-regulation of cytokine and other metabolites of primary and secondary metabolism [36][37][38][39]. While flesh firmness may play a crucial role in watermelon quality and may also contribute to longer shelf life, the rind thickness of the watermelon fruit by rule affects the post-harvest management and postharvest performance of the fruit [9].…”
Section: Fruit Pulp Texture and Rind Thicknessmentioning
confidence: 99%
“…Pectin is an important component of plant cell wall and plays an important role in maintaining cell wall stability and resistance to adversity, accounting for 35% of the cell wall components of dicotyledons [ 81 ]. Pectinesterase (PME) mainly catalyze the demethylation of pectin to form pectic acid and methanol [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hemicellulose, epicarp and mesocarp tissues contain an increased amount of different XyG monosaccharides, suggesting that pre-anthesis CPPU applications could promote xyloglucan synthesis during grape berry development. Homogalacturonan is the pectinic domain of cell wall components most widely associated with firmness in different berry fruits [2,27,[50][51][52]. The analyses indicate that pre-anthesis CPPU applications induce an increased accumulation of GalA and cell wall-associated calcium than control samples in the mesocarp tissue.…”
Section: Early Cppu Treatment Changes Cell Wall Composition and Promotes An Increase In Berry Firmness At Harvestmentioning
confidence: 95%